1976
DOI: 10.1002/jlcr.2580120209
|View full text |Cite
|
Sign up to set email alerts
|

Non specificite de marquage dans le cas de tritiation par deshalogenatlon catalytique: Cas de la papaverine

Abstract: The tritium l a b e l l i n g of papaverine by c a t a l y t i c deshalogenation of monobromopapaverine gives a compound whereof the s p e c i f i c r a d i o a c t i v i t y i s 43 Ci/mM. Our r e s u l t s have shown t h a t only 49 X of t h i s r a d i o a c t i v i t y came from the s u b s t i t ut i o n of bromine by tritium ; 46 X are located i n the methylen group while the remaining 5 % are d i s t r i b u t e d over the o t h e r p o s i t i o n s . R6SUdLe marquage au tritium de l a papavgrine p a r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In addition to the expected tritium in the 4 position in the A ring, tritium NMR (Figure 4, [H n ] PF‐622d ) analysis also indicated that additional tritium was present in the benzylic position, which is not unexpected from the literature precedence. The result further indicated that under 10% Pd/C catalytic condition, the catalytic H‐T exchange as a side reaction took place at certain active positions mentioned above, a similar observation of which was reported by Devillers (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the expected tritium in the 4 position in the A ring, tritium NMR (Figure 4, [H n ] PF‐622d ) analysis also indicated that additional tritium was present in the benzylic position, which is not unexpected from the literature precedence. The result further indicated that under 10% Pd/C catalytic condition, the catalytic H‐T exchange as a side reaction took place at certain active positions mentioned above, a similar observation of which was reported by Devillers (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…Although tritium‐labeled compounds can be prepared by multistep chemical synthesis, as are carbon‐14‐labeled compounds, a more ideal approach is to use the method of metal catalyzed hydrogen isotope exchange to introduce tritium into the final product. Several effective metal catalysts were developed for “fast” tritium labeling of drugs, such as H‐T exchange and tritiodehalogenation . This paper details the specific radiosynthesis of 3 tritium isotopomers (Figure 1) in the presence of commercially available catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papaverine ( 12 ), isolated from the opium poppy, has a vastly different structure and pharmacology compared with the usual poppy‐produced morphinan alkaloids. Papaverine has been tritium labelled at a surprisingly higher than expected specific activity by means of a bromination‐catalytic tritium dehalogenation method . An explanation for this specific activity anomaly was provided by oxidative degradation studies, which indicated that about half of the incorporated tritium had been installed at the relatively acidic bisbenzyl methylene position of papaverine by a general exchange mechanism.…”
Section: Quinoline and Isoquinoline Alkaloidsmentioning
confidence: 99%
“…Papaverine has been tritium labelled at a surprisingly higher than expected specific activity by means of a bromination-catalytic tritium dehalogenation method. 59 An explanation for this specific activity anomaly was provided by oxidative degradation studies, which indicated that about half of the incorporated tritium had been installed at the relatively acidic bisbenzyl methylene position of papaverine by a general exchange mechanism. [ 3 H]Papaverine has been effectively used for animal metabolic studies.…”
Section: Quinoline and Isoquinoline Alkaloidsmentioning
confidence: 99%